Acoustic barionic scale in z_eff = 0,166 with blue galaxies from SDSS - Lima, Hanna; Nunes, Rafael; Avila, Felipe; Carvalho, Edilson; Bernui, Armando (Cadernos de Astronomia, 2026)
Work presented at the event As Astrocientistas: III Encontro Brasiliero de Meninas e Mulheres da Astrofísica, Cosmologia e Gravitação, held between March 31 and April 4, 2025.